Individual And Environmental Factors Associated With Physical Activity Practices Among Adolescents Of Devchuli Municipality - Acharya, Aashish (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Background: Regular physical activity helps children and adolescents to remain healthy and fit, improve muscular and cardiorespiratory fitness, have psycho-social benefits The Global School Based Student Health Survey of Nepal 2015 shows that only 15.1% of adolescents of age 13-17 years were physically active daily. The risk factor of chronic diseases are traced back up to childhood hence promoting physical activity should start from childhood. Identification of these factors that affects level of physical activity among adolescents of Nepal and its better understanding will aid in promoting physically active lifestyle and designing effective interventions.